ANALISIS PENENTUAN KEPENTINGAN JALAN POROS KABUPATEN ANTAR KECAMATAN DI KABUPATEN TRENGGALEK UNTUK MENDUKUNG PENGEMBANGAN WILAYAH - Catur Widiasmoro; Hitapriya Suprayitno; Eko Budi Santoso (Institut Teknologi Sepuluh Nopember (ITS), 2018)
Infrastructure has a very important role as certain to instigates economic growth and regional development.Transportation serves facility for production and investment systems that enables regional services and activities. Regiondeveloped on potential itself, to support it how determines best alternative of road links is required. To obtain weight ofcriteria in this research using pairwise comparison, and furthermore the Technique for Order Preference by Similarity toIdeal Solution is used to discover preference value from each road links. This research indicates that preference inter-districtsroad Bendo-Surodakan is the main priority with value of preference 3,07, then Suruh-Pule, Gandusari-Kampak road link withscore 2,44 and 2,30, consecutively. Road link with lowest score obtained by Bangunsari-Bulu as 0,057